2014
DOI: 10.1111/1574-6941.12369
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of bacterial and archaeal symbionts in high and low microbial abundance sponges using real-time PCR

Abstract: In spite of considerable insights into the microbial diversity of marine sponges, quantitative information on microbial abundances and community composition remains scarce. Here, we established qPCR assays for the specific quantification of four bacterial phyla of representative sponge symbionts as well as the kingdoms Eubacteria and Archaea. We could show that the 16S rRNA gene numbers of Archaea, Chloroflexi, and the candidate phylum Poribacteria were 4-6 orders of magnitude higher in high microbial abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 62 publications
4
71
0
1
Order By: Relevance
“…Members of Chloroflexi are members of HMA sponge microbiomes, with representatives of classes SAR202, Anaerolineae, and Caldilineae, being most abundant (32). Visualization of Chloroflexi by fluorescence in situ hybridization (FISH) revealed bright and abundant signals (33, 34). Because Chloroflexi likely play an important role in the HMA sponge holobiont, we aimed (i) to assess the relative abundances and distribution in diverse HMA sponge species by using the largest dataset currently available (EMP sponge microbiome), (ii) to provide an updated phylogenetic analysis, (iii) to characterize the functional gene repertoire with a particular focus on carbon degradation and symbiotic lifestyle, and, (iv) to visualize Chloroflexi in mesohyl tissues at ultrastructural resolution by FISH-CLEM methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Members of Chloroflexi are members of HMA sponge microbiomes, with representatives of classes SAR202, Anaerolineae, and Caldilineae, being most abundant (32). Visualization of Chloroflexi by fluorescence in situ hybridization (FISH) revealed bright and abundant signals (33, 34). Because Chloroflexi likely play an important role in the HMA sponge holobiont, we aimed (i) to assess the relative abundances and distribution in diverse HMA sponge species by using the largest dataset currently available (EMP sponge microbiome), (ii) to provide an updated phylogenetic analysis, (iii) to characterize the functional gene repertoire with a particular focus on carbon degradation and symbiotic lifestyle, and, (iv) to visualize Chloroflexi in mesohyl tissues at ultrastructural resolution by FISH-CLEM methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic trees constructed from partial 16S rRNA sequences suggest that sponge-associated Poribacteria may fall into four [16,23] or five [24] distinct subclasses, but no correlations have been observed between these classes and sponge host taxonomy or geographical location. Several studies analyzing sponge-associated microbial communities with specifically targeted 16S rRNA gene primers observed Poribacteria-related sequences at relative abundances of 20-30% [1,12,[25][26][27]. Other studies, using only broader "universal" primers, found much lower relative abundances in samples from the same sponge host species [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…The methods used to analyze soil microflora include cultivation of microorganisms on differential media, realtime taxon-specific PCR (RT PCR), metagenomic sequencing of evolutionary conserved sequences, transcriptomic, proteomic and other methods [1,2]. The strengths of taxon-specific RT PCR include rapidity and relatively low cost of analysis, the simplicity of sample preparation, processing and interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%